Gingivitis in cattle and supplemental protein diet: Insights from proteomic analysis - Saraiva, Júlia Rebecca [UNESP]; Dionizio, Aline; Borsanelli, Ana Carolina; Ventura, Talita Mendes Silva; Thomassian, Larissa Tercilia Grizzo; Athayde, Flávia Regina Florencio [UNESP]; Vaccari, Juliana [UNESP]; Ramos, Thamiris Naiasha Minari [UNESP]; de Souza, Natália Cristina; Buzalaf, Marília Afonso Rabelo; Dutra, Iveraldo S. [UNESP] (Elsevier, 2023)
Salivary proteins are essencial in the maintenance of oral homeostasis and can reflect systemic and localized processes, like gingivitis. However, little is known about the relationship between diet and the occurrence of gingivitis in cattle. The present study aimed to characterize the salivary proteomic profile of cattle (n = 12) fed hay (112.19 g/kg of crude protein) cultivated in reformed pastures, and, one group received protein supplement (PS, n = 6); the effect of the protein supplement on the gingival health of the cattle was determined by weekly intraoral examination and periodontal evaluation of the eight (deciduous) incisors. The whole saliva proteome of the two groups was evaluated after 20 and 60 days of confinement. In the periodontal clinical evaluation both groups had episodes of gingivitis; however, the average number of affected sites in the PS group was higher on day 60. The cattle fed exclusively hay, presented a lower average of affected gingival sites on day 60. After 60 days of experimentation, nine biological and 11 immunological processes were altered in bovine saliva. Proteins with multiple functions were detected in the saliva of the cattle; however, differences were observed in their regulation between the two groups. Significance: In bovine populations, the relationship between diet and increased incidence of gingivitis is theorized. The results of the present pilot study, both diets caused episodes of gingivitis in the primary dentition of cattle and, apparently, diets with protein supplementation stimulate the expression of salivary proteins with a protective role in cattle that can act against infectious-inflammatory processes, such as gingivitis. However, it is plausible that over time, cattle will adapt to these diets and become more vulnerable to gingivitis.
Keywords: Bovine; Diet; Gingivitis; Proteomic; Saliva